SYNONYMOUS FEATURES OF NATIVE AND BORROWED WORDS IN THE UZBEK LANGUAGE (Academicia Globe: Inderscience Research, 2021)
This article gives popular views on language, language enrichment and the role of borrowing in it and highlights the features of Uzbek native words. It presents the definitions of some selected native and borrowed words, which have the same meaning, and explains their usage area. The article gives a comprehensive comparative and lexical analysis of the selected words and this research learns the synonymic character of borrowings with native words.